Plant breeding notes: A new article type for plant-environment interactions - Ingram, Jonathan; Jenkins, Gareth B.; Ismail, Abdelbagi; Léon, Jens; Ordon, Frank (Wiley, 2025)
Plant breeding covers a wide range of research critically important for the advancement of agriculture worldwide. In-depth research articles usually form the version of record for disseminating new developments, but for more limited, sometimes highly specialist studies, a simpler research note may be sufficient and more appropriate. This is the thinking behind a new short article category for Plant-Environment Interactions, Plant Breeding Notes, with the aim of bringing useful information for plant breeders to publication simply and quickly for our authors.